SAT0086 Evaluation of diagnostic performance of magnetic resonance imaging (MRI) and ultrasound (US) toward early rheumatoid arthritis from nagasaki early arthritis cohort. (12th June 2018) - Takatani, A.; Tamai, M.; Ohki, N.; Nakashima, Y.; Endo, Y.; Tsuji, S.; Shimizu, T.; Umeda, M.; Fukui, S.; Sumiyoshi, R.; Nishino, A.; Koga, T.; et al.
Abstract : Background: We previously reported that the presence of autoantibodies, magnetic resonance imaging (MRI) bone oedema, ultrasound (US) power Doppler (PD) &x2267; grade 2 articular synovitis are indispensable markers to predict the development of RA from undifferentiated arthritis whereas combination analysis used by the above variables, focusing on very early phase of arthritis, remains to be done in our cohort. Objectives: To investigate and re-confirm the diagnostic performance of autoantibodies, MRI findings and US findings toward early RA from NAGASAKI EARLY ARTHRITIS COHORT. Methods: One hundred and three patients, suffering arthralgia less than 6 months and examined by both MRI and US of wrist and finger joints, were selected from NAGASAKI EARLY ARTHRITIS COHORT dating from September 2009 to August 2017. US were evaluated by synovitis score of semi-quantitative manner by gray-scale (GS) and power Doppler (PD) proposed from EULAR. In MRI, synovitis, bone oedema and bone erosion were assessed by the Rheumatoid Arthritis Magnetic Resonance Imaging Scoring system (RAMRIS). After univariate analysis, multivariate analysis was employed to clarify the diagnostic predictors of early RA. Results: Median of age was 60 years and that of symptomatic duration was 2 months. Female was 68.9%, positive rate of RF was 64.7% and that of ACPA was 47.1%. Total GS score was 4.0, total PD score 2.0, MRI synovitis score 3.0, MRI bone oedema score 0, MRI bone erosion score 0. Seventy patients were diagnosed as early RA during follow-up periods. A univariate analysis showed ACPA, CRP, MMP-3, fulfilment of 2010 ACR/EULAR criteria, MRI synovitis score, MRI bone oedema score, total GS score, total PD score and PD &x2267; grade 2 articular synovitis were associated with early RA. Multivariate analysis revealed ACPA and PD &x2267; grade 2 articular synovitis at any joints were independent predictors toward diagnosis of early RA. Conclusions: Our present study re-confirms the importance of ACPA, PD &x2267; grade 2 articular synovitis and MRI bone oedema, especially the former two, to predict the development of early RA from undifferentiated arthritis patients. Disclosure of Interest: None declared